2017
DOI: 10.21276/aimdr.2017.3.4.sg3
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report on Perforated Meckel’s Diverticulitis Mimicking Acute Appendicitis

Abstract: Meckel's diverticulum, the most common congenital anomaly of small bowel although usually silent, can cause complications like intestinal obstruction, bleeding, diverticulitis, perforation etc. We report a case, which presented with acute onset of abdominal pain which was clinically and sonographycally diagnosed as acute appendicitis. Abdomen was explored with a midline incision, as X-ray abdomen showed free gas under diaphragm and a perforated Meckel's diverticulum was found which was managed by resection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…However, it may cause bleeding, obstruction, inflammation, or perforation. 23 In our study 0.4% of cases had Meckel diverticulum.…”
Section: Discussionsupporting
confidence: 46%
“…However, it may cause bleeding, obstruction, inflammation, or perforation. 23 In our study 0.4% of cases had Meckel diverticulum.…”
Section: Discussionsupporting
confidence: 46%
“…In our study, all cases of Meckel’s diverticulum involved in intussusception were found to be of this morphology. Inflamed Meckel’s diverticulum may present with abdominal pain mimicking simple or complicated appendicitis [ 12 , 13 ]. In our study, there were nine cases that were initially diagnosed as acute appendicitis but per-operatively proved to be Meckel’s diverticulitis.…”
Section: Discussionmentioning
confidence: 99%